Revitalisasi Peran Keluarga dalam Pendidikan Anak : Model Pendampingan Belajar di Desa Unse - Presi Nila Sari (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2025)
This research aims to examine the revitalization of the family’s role in children’s education through the development of a learning assistance model in Unse Village. The role of the family as the primary educator has often diminished due to modernization, parents’ busy schedules, and the increasing reliance on formal schools. However, children’s education does not only take place in classrooms but also within everyday interactions at home. Using a qualitative approach with observation, in-depth interviews, and documentation methods, this study found that family involvement in children’s learning significantly influences their motivation, discipline, and academic achievement. The developed learning assistance model emphasizes three main aspects. First, joint study activities that actively engage parents in helping children with assignments and reading. Second, strengthening family communication that fosters warmth, self-confidence, and emotional support for children. Third, the integration of religious and local cultural values into family routines, ensuring children receive balanced education across cognitive, affective, and spiritual domains. The implications of this study indicate that families, schools, and communities must collaborate to build a more holistic educational ecosystem in Unse Village. Revitalizing the family’s role not only improves children’s learning quality but also strengthens cultural identity and social bonds within the community. Thus, family-based learning assistance can serve as an alternative educational model that is highly relevant for rural contexts in Indonesia.